FDI and unemployment, a growth perspective - Ignat Stepanok (Review of International Economics, 2022)
North–South foreign direct investment (FDI) is frequently viewed as a process in which jobs relocate from the North to the South. I build a growth model with two asymmetric trading economies, the North where firms innovate and the South where Northern firms invest to take advantage of lower wages. Contrary to expectation, I find that lower FDI costs increase unemployment both in the North and in the South. There are two effects of FDI on unemployment, a direct positive one which contributes to the turnover of firms parallel to innovation. The indirect effect appears through innovation and growth: more FDI means higher innovation, this intensifies firm turnover and increases the unemployment rates in both countries even further. I solve the model analytically without trade costs and imitation of products in the South. For the version with trade costs and imitation I offer a numerical solution in which I also look at the effect of FDI on welfare and find a positive relation. In addition to FDI, I explore how intellectual property (IP) rights protection affects unemployment and welfare. Both are higher in a steady state with stricter IP protection.
Keywords: 330; creative destruction; foreign direct investment; intellectual property rights; North–South trade; unemployment